Process evaluation for isolation and storage of a native entomopathogenic nematode Steinernema feltiae (Rhabdithida: Steinernematidae) - SÁENZ, ADRIANA (Revista Colombiana de Entomología, 1999)
Known the importance those have the entomonematodes as agents of biological control and given the techniques used for isolation and storage at world level, were evaluated different procedures that permitted the manipulation of the infective juveniles (J3) recovered. Therefore, from samples collected in three areas cultivated with potato in the vereda Casablanca (Villapinzón -Cundinamarca -Colombia), working with an insect trap modified technique (TBA) and solutions of Baermann funnel (TIB), the entornonematode Steinernema feltiae Filipjev, 1934, were isolated with larvae of the last instar of the greater moth from the beehives Galleria mellonella, then adjusting suspensions of 200 nematodes/ ml, consequently obtaining infective juveniles (J3), to evaluate three solutions of them that were going to be storage, for a period six month. Therefore of 300 exposed larvae with the technical TBA, just 27 (23%), were found parasitized for S. feltiae and with TIB were obtained 12881 nematodes pertaining to Rhabditidae (7024), Steinernematidae (3297), Dorylaimidae (943), Panagrolaimidae (962) and Tylenchidae (654) families; just 25 of 300 exposed larvae were affected by J3 of S. feltiae. In the storage assay done was possible to establish that the solution of ml of distilled -water and 30 µl of TritonX100 up to 10°C, permitted the infective juveniles to survive for six months, without affecting the pathogenicity on last instar larvae of G. mellonella.